Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan - Kristiawan, Dedy; Widodo, Nurul Sapta (Universitas Hang Tuah, 2020)
The purpose of this study was to examine and analyze the effect of Transformational Leadership, Organizational Culture, and Organizational Citizenship Behavior simultaneously and partially on employee performance. This type of research is an associative study that explains the relationship and influence between the variables of Transformational Leadership, Organizational Culture, and Organizational Citizenship Behavior on employee performance. The population in this study amounted to 71 people. The sampling technique used the saturated sampling method (census method). Methods of data collection by interview, literature study, observation, and questionnaires. The data analysis technique was performed using the multiple linear regression method. Based on the results of the research and data analysis it was concluded that; (1) Simultaneously, Transformational Leadership, Organizational Culture, and Organizational Citizenship Behavior variables have a significant effect on employee performance. (2) based on the partial t test, Transformational Leadership and Organizational Culture have a significant effect on employee performance. (3) the Organizational Citizenship Behavior variable has no significant effect on employee performance.